Ethics of Alterity, Confrontation and Responsibility in 19th- to 21st-Century British literature - Ganteau, Jean-Michel; Reynier, Christine (Horizons anglophones, 2013)
Over the last few decades, in the wake of the 'Ethical Turn', contemporary literature has been examined through the prism of the ethics of alterity. Yet, this may not be consistently the case with Victorian and Modernist literature, since relatively few of the authors of those periods have elicited such critical and theoretical scrutiny. The articles in this volume set off to re-read Victorian and Modernist literature in the light of the ethics of alterity and investigate whether the post-Auschwitz, contemporary period breaks away from or favours lines of continuity with the productions of the earlier era. It also strives to address works which do not belong to the canon, focusing alternately on great authors and less known artists, on what has been termed 'minor' texts or genres that are less visible than the novel. Approaching literature by examining the relations between ethics and aesthetics, even while adopting an ethical approach, helps the authors in this volume contribute to revising the contemporary, Modernist and Victorian canon in English Literature.